“Crumbs of Kindness” : a strategic public communication campaign for Food from the Heart, a voluntary food distribution programme. - Ng, Chee Shen. (2008)
(This FYP consists of 3 sections) This is an awareness campaign aims to increase knowledge and interest of Food from the Heart's activities and to promote the social cause of helping the poor and needy through providing food items via media publicity and public events.